A randomized trial on the effects of flavorings on the health benefits of daily peanut consumption. Issue 3 (18th December 2013) - Jones, Joshua B; Provost, Marion; Keaver, Laura; Breen, Claire; Ludy, Mary-Jon; Mattes, Richard D
ABSTRACT: Background: Chronic peanut consumption is associated with health benefits. To encourage consumption, peanuts are marketed with various flavorings, but questions have been raised as to whether seasonings offset the benefits of peanuts alone. Objective: This study sought to determine whether flavorings on peanuts affect health benefits over 12 wk. Design: In a randomized, parallel-group trial, 151 participants received 42 g peanuts/d as 14-g servings of 3 different flavors ( n = 50) or a single flavor ( n = 25–26/group). Anthropometric indexes, blood pressure, and heart rate were measured biweekly. Cardiovascular disease risk factors (serum lipids, insulin, glucose, and cortisol) were assessed monthly. Results: No single added flavor differentially altered body weight, body fat, body mass index, heart rate, or blood indexes in the total sample. Participants at greater risk of cardiovascular disease had significantly greater mean (±SE) reductions in diastolic blood pressure (−5.0 ± 1.7 mm Hg compared with −0.7 ± 0.6 mm Hg), cholesterol (−12.1 ± 8.5 mg/dL compared with +5.6 ± 2.0 mg/dL), and triglycerides (−31.7 ± 15.8 mg/dL compared with +2.3 ± 3.0 mg/dL) ( n = 27, 24, and 15, respectively; P < 0.01) than did those at lower risk, who did not have significantly different cholesterol or triglyceride concentrations. Consumption of a variety of flavors led to greater weight gain (0.9 ± 0.3 kg) compared with individual flavors alone (0.5 ± 0.2 kg) ( P < 0.05), but increases in fat and lean masses were not significant. Conclusions: Regardless of flavoring, peanut consumption offered significant benefits to participants with elevated serum lipids and blood pressure. Sensory variety led to a small, but significant, increase in body weight in comparison with ingestion of a single flavor but no change in fat mass. This trial was registered at http://www.clinicaltrials.gov as NCT01886326.